2016
DOI: 10.1590/0074-02760150306
|View full text |Cite
|
Sign up to set email alerts
|

A molecular platform for the diagnosis of multidrug-resistant and pre-extensively drug-resistant tuberculosis based on single nucleotide polymorphism mutations present in Colombian isolates of Mycobacterium tuberculosis

Abstract: Developing a fast, inexpensive, and specific test that reflects the mutations present in Mycobacterium tuberculosis isolates according to geographic region is the main challenge for drug-resistant tuberculosis (TB) control. The objective of this study was to develop a molecular platform to make a rapid diagnosis of multidrug-resistant (MDR) and extensively drug-resistant TB based on single nucleotide polymorphism (SNP) mutations present in therpoB, katG, inhA,ahpC, and gyrA genes from Colombian M. tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…These results were similar to those of previous studies [26,32,33]. The frequency of this mutation in this study was 79% (41/52) whereas other studies reported frequencies of 27% [24], 64% [29] and 60% [30]. The second most common mutation was His526Tyr (7.8%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were similar to those of previous studies [26,32,33]. The frequency of this mutation in this study was 79% (41/52) whereas other studies reported frequencies of 27% [24], 64% [29] and 60% [30]. The second most common mutation was His526Tyr (7.8%).…”
Section: Discussionsupporting
confidence: 91%
“…From a previous report from the USA, Thailand and Korea, the frequency of -15 (C>T) point mutations is 39%, 14% and 25%, respectively [22,26,27]. Therefore, eight strains from this study without the mutation in katG_Ser315Thr inhA_and -15 (C>T) may carry mutations located in other katG or inhA loci [28,29] or other associated genes such as ahpC and ndh gene [30]. However, the mutations katG_Ser315Thr and inhA_-15 (C>T), both of which showed high sensitivity (89%) and high specificity (100%), could be used as indicators for detecting INH resistance.…”
Section: Discussionmentioning
confidence: 63%
“…En conclusión, las pruebas moleculares no reemplazan los métodos convencionales, sin embargo, son un eficiente mé-todo de tamizaje cuando se combinan con datos clínicos y epidemiológicos, impactando significativamente en una diagnosis temprana de la resistencia, lo que contribuye a estrategias de control de la resistencia de TB en los países 44 . De igual manera, investigaciones dirigidas al estudio de la resistencia por secuenciamiento del genoma completo ayudarían en el futuro a dilucidar los mecanismos moleculares de resistencia a isoniacida u otros medicamentos en aislados de Mycobacterium tuberculosis circulantes en el Ecuador [45][46][47] .…”
Section: Nuestros Resultados Mostraron Que Al Emplear Las Enzimasunclassified